PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN BISNIS ONLINE KELAS XI BDP SMK MUHAMMADIYAH 2 PEKANBARU - Iswandi Iswandi; Caska Caska; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research purpose to determine the influence of learning independence on student learning outcomes on the Online Business lesson of XI BDP student’s class of SMK Muhammadiyah 2 Pekanbaru. The data of research collection used were documentation to get learning outcomes students and questionnaire to get data of learning independence. The population in this research was students of XI BDP class, consisting of 30 students. Sampling in this population using the technique until saturated that is where the entire population become sample that amount to 30 students. The collected data is then tabulated and analyzed using simple linear regression with the help of SPSS version 22. The results descriptively indicate that the learning outcomes of online business subjects are categorized enough amounting to 16 students (53%) and high learning independence categorized as high as 25 students (83%). The results of research are there is a positive effect of learning independence on student learning outcomes by the contributed of 28,8%, meanwhile the rest was 71,2% which was affected by another factor that was not included in this research.Key word : Learning Independence, Learning Outcomes